THE FACTOR INFLUENCES STUDENT’S ONLINE PURCHASING EXPERIENCES ACROSS A VARIETY OF SOCIAL MEDIA PLATFORMS (Jurnal Pembangunan Sosial, 2024)
This study examines the experiences of students at a university in northern Malaysia who make online purchases using social media platforms such as Facebook, TikTok, and Instagram. TikTok, and Instagram. Social media has become an important online shopping platform due to the rapid growth of e-commerce, and it has a huge impact on consumer behavior, especially for younger consumers.The aim of the study is to understand what motivates students to use different social media platforms to make their online purchases, as well as the benefits and difficulties encountered and the satisfaction obtained. There are three objectives studied in this study, which are to identify the factor of perceived usefulness that influences student’s online purchase intention, to identify the factor of perceived of ease-ofuse that influences student’s online purchase intention and to identify the factor of trust that influences students’ online purchase intention. This study was conducted using a thematic analysis, involving a total of seven university students as respondents. The results of the analysis show that there are five factors that influence online purchase decisions. The five factors are: demonstration factors, comments, convenience, trustworthiness, and engaging content. The findings of this study have successfully answered the research questions and research objectives as mentioned before.